KONSTRUKSI BUDAYA SEBAGAI DAYA TARIK WISATA: ANTARA RELIGI, IMAJINASI, DAN MASYARAKAT GUNUNG KAWI - Suryani; Fitria, Annisa Diva (PARIWISATA BUDAYA: JURNAL ILMIAH PARIWISATA AGAMA DAN BUDAYA, 2026)
Pesarean Gunung Kawi offers a unique religious tourism experience that blends Javanese and Chinese culture. This place is known as a pilgrimage site not only for Muslims but also for the Chinese community. The long history of Pesarean Gunung Kawi has made it a tourist destination with a high level of religious tolerance. The cultural construction of this tourist destination is inevitable given the need to attract tourists. The dialectic between religious elements, imagination, and the active role of the local community has contributed to the survival of this tourist location until now. Using qualitative methods, this study began with participant observation of several cultural activities there. It was also supported by in-depth interviews with three key informants to strengthen the data to be explored. The results of the study show that traditions are not only preserved but can also be dynamically constructed into tourist attractions. The religious values embraced by the local community are combined with mystical narratives that shape the collective imagination. This imagination is manifested in rituals such as ngalap berkah. Rituals and imagination then become tourist commodities that attract pilgrims to come. The local community also plays an active role in creating a space for negotiation where spiritual values are related to the logic of tourism. This is not only to satisfy the imagination of tourists but also to sustain the local economy. The results of the study are expected to provide new dynamics on how culture is not a fixed relic but a process that is continuously negotiated by the community without diminishing the meaning or value of the culture itself.